Mitigating Strawberry Generation Risks Through Multiple Learning Strategies in Kindergarten - Apriyansyah, Chandra; Sukatmi, Sri; Mustafa, Lily Muliana (Universitas Nahdlatul Ulama Surabaya, 2023)
The efforts made by early childhood education teachers to address the risks associated with